The Emerging Role of Exosomes in Epithelial–Mesenchymal-Transition in Cancer - Vella, Laura Jayne (Frontiers in Oncology, 2014)
Metastasis in cancer consists of multiple steps, including Epithelial-Mesenchymal-Transition (EMT), which is characterized by the loss of Epithelial-like characteristics and the gain of Mesenchymal-like attributes including cell migration and invasion. It is clear that the tumour microenvironment can promote the metastatic cascade and that intercellular communication is necessary for this to occur. Exosomes are small membranous vesicles secreted by most cell types into the extracellular environment and they are important communicators in the tumour microenvironment. They promote angiogenesis, invasion and proliferation in recipient cells to support tumour growth and a prometastatic phenotype. Although it is clear that exosomes contribute to cancer cell plasticity, experimental evidence to define exosome induced plasticity as EMT is only just coming to light. This review will discuss recent research on exosomal regulation of the EMT process in the tumour microenvironment.